Prevalence of Depression and Anxiety among Women with Polycystic Ovary Syndrome and their Association with Hormonal and Metabolic Parameters - Khan, Muhammad Muslim; Fatima, Fatima; Naila, Naila; Jamal, Izaz; Gul, Ijaz; Muneeb, Pirzada (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Polycystic ovary syndrome (PCOS) remains one of the most common endocrine disorders in women of reproductive age. PCOS encompasses a variety of symptoms across multiple domains, including frank reproductive, metabolic, and psychological disturbances. Numerous studies suggest a greater occurrence of depression and anxiety in women with PCOS, which may be a result of the endocrine perturbations, insulin resistance, dysregulated body fat, and metabolic syndrome. These comorbidities affect the women’s quality of life and likely hinder their overall health and well-being. Moreover, psychological comorbidities in women with PCOS affect treatment compliance and health outcomes over an extended period. Objectives: To ascertain the levels of incidence of depression and anxiety in women suffering from PCOS and the relationship of these conditions with certain hormonal and metabolic variables. Methodology: This cross-sectional study examined women aged 18–45 years diagnosed with PCOS and seen in a tertiary gynecology clinic. Using standard tools, depression and anxiety were measured. Participants had their anthropometric measures taken, and a blood draw was done to test for hormonal levels (total testosterone, luteinizing hormone, follicle-stimulating hormone) and for metabolic variables (fasting glucose, fasting insulin, HOMA-IR, lipid profile). The information was analyzed in SPSS, with statistical significance accepted if p was < 0.05. Results: A total of 130 women with PCOS were included, with a mean age of 26.8 ± 5.4 years. Depression was observed in 38.5% of participants, while anxiety was present in 42.3%. Women with depression demonstrated significantly higher body mass index and HOMA-IR values compared to those without depression (p=0.01). Anxiety showed a significant association with elevated total testosterone levels and dyslipidemia (p=0.02). Increasing insulin resistance and hyperandrogenism were significantly correlated with higher depression and anxiety scores. Conclusion: Evidence suggests that women who have PCOS are at higher risk of having depression and anxiety. This is often linked to factors such as depression, adverse metabolic factors, and insulin resistance. Screening for mental health and psychological comorbidities as part of the metabolic and endocrine workup in women with PCOS is vital to provide complete care.